2020
DOI: 10.1029/2020gl090167
|View full text |Cite
|
Sign up to set email alerts
|

Increased Aerosol Extinction Efficiency Hinders Visibility Improvement in Eastern China

Abstract: Though China has witnessed substantial particular matter pollution mitigation owing to the strict emission control in recent years, the frequency of haze events with low visibility is not improved as much as expected, especially in cold seasons. Here, 6-year wintertime observations, satellite retrievals, a thermodynamic model, and theoretical calculation were integrated to better understand the complex influence of aerosol chemical composition and hygroscopic behaviors on visibility impairment. We found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…In addition, the hydrolysis of N 2 O 5 also plays a crucial role in nitrate formation, which influences the conversion of N 2 O 5 to nitrate (Wang, Chen, et al., 2020; Wen et al., 2018; Sun et al., 2018). Elevated nitrate proportion in PM 2.5 has been demonstrated to promote N 2 O 5 hydrolysis by combining the slightly increased RH (Liu et al., 2020; Y. Wang et al., 2020). Figure S9 in Supporting Information shows the variations of aerosol liquid water content (ALWC) as a function of nitrate proportion in PM 2.5 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the hydrolysis of N 2 O 5 also plays a crucial role in nitrate formation, which influences the conversion of N 2 O 5 to nitrate (Wang, Chen, et al., 2020; Wen et al., 2018; Sun et al., 2018). Elevated nitrate proportion in PM 2.5 has been demonstrated to promote N 2 O 5 hydrolysis by combining the slightly increased RH (Liu et al., 2020; Y. Wang et al., 2020). Figure S9 in Supporting Information shows the variations of aerosol liquid water content (ALWC) as a function of nitrate proportion in PM 2.5 .…”
Section: Resultsmentioning
confidence: 99%
“…We inferred that the high values of α e f f 2.5 were caused by the changes in the size and composition of aerosols. Liu et al [45] confirmed that the MEE in Nanjing, China, increased from 7.1 m 2 g −1 in 2013 to 9.3 m 2 g −1 in 2018. Joo et al [46] also stated that the MEE of PM 2.5 increased by 0.72 m 2 g −1 annually during 2015-2019.…”
Section: Mass Extinction Efficiencymentioning
confidence: 94%
“…Second, we did not consider the effects of relative humidity. Many studies confirmed that relative humidity has a high impact on visibility [30,35,36,[42][43][44][45][46]. The correlation coefficient of the mass concentration of PM 2.5 and visibility data increased from 0.81 to 0.89 when correcting for the relative humidity [47].…”
Section: Extinction Coefficientmentioning
confidence: 95%
“…On the other hand, fewer air pollutions do not directly bring in more blue skies, considering days with higher cloud cover or precipitation. The inconsistency between dropping PM and unchanged low visibility events (Ding et al 2016 ) can be seen even during the COVID-19 lockdown period (Huang et al 2020b ; Huang et al 2020c ; Liu et al 2020 ). All mentioned above try to convey the non-synergy correlation between air pollution and blue days when considering the unfavorable meteorological conditions dominated by large-scale synoptic circulation (Bei et al 2020a ).…”
Section: Introductionmentioning
confidence: 99%